At the Heart of the Union
XII, 328 p.
Keywords: The European Commission is very much at the heart of the European Union. Its wide variety of roles make it the institution most readily identified with the Union's many different activities. Surprisingly, relatively little has been written about this vital European institution. This book makes a major contribution to furthering understanding of the Commission. A broad range of different perspectives based on new research cover all aspects of its nature and functioning.